Metacognitive training for patients with schizophrenia (MCT): feasibility and preliminary evidence for its efficacy - Aghotor, Julia; Pfüller, Ute; Moritz, Steffen; Weisbrod, Matthias; Roesch-Ely, Daniela (Journal of behavior therapy and experimental psychiatry, 2010)
Background - The treatment program “Metacognitive training for patients with schizophrenia” (MCT) addresses cognitive deficits and biases assumed to play a crucial role in the pathogenesis of delusions (e.g. jumping to conclusions, theory of mind deficits, bias against disconfirmatory evidence). The feasibility of this approach and its effects on positive symptoms and cognitive biases were investigated in this pilot study. - Methods - Thirty inpatients of the Department of Psychiatry of the University Hospital Heidelberg with a schizophrenia spectrum diagnosis were randomly assigned to either MCT or an active control intervention. Both training programs were carried out over a time period of four weeks. Psychopathological, cognitive and metacognitive measures were collected at baseline and after completion of the training. Schizophrenia symptoms were determined blind to group allocation with the Positive and Negative Syndrome Scale (PANSS). - Results - No adverse reactions were noted in the MCT group and patients expressed a greater subjective training success relative to the control condition (d = .57). A stronger improvement on all PANSS subscales was found at a descriptive level; positive symptoms attenuated under MCT with a medium effect size of d = .43. In addition, results showed a reduced jumping to conclusions bias for MCT patients (d = .31). However, none of the effects reached statistical significance. Optimal sample size was calculated for future studies. - Conclusion - The present study confirms the feasibility of MCT and provides preliminary evidence for its efficacy ameliorating positive symptoms and the jumping to conclusions bias.
Gesehen am 09.12.2021